Amazon in business to customers and overcoming obstacles - Yousef A. Baker, El-Ebiary; Syarilla Iryani, A. Saany; Abdullah, Altrad; Pathmanathan, P.R.; Yazeed, Al Moaiad; Yousef, Mohamed Endara; Khairi, Aseh; Mazen, Mohammed Farea; Nurul Adilah, Abdul Latiff (2021)
Electronic commerce, or people call it e-commerce, it refers to buying and selling products or services on the Internet and transferring money and data to carry out these transactions. More consumers are shifting from traditional transactions to e-commerce, as e-commerce becomes faster and cheaper. In contrast, electronic commerce provides more ease and variety in the composition of goods and services worldwide. E-commerce is the type of electronic business that has been in business for more than 25 years and is used by many users around the world. This research aims to shed light on the nature of electronic commerce and the difficulties it faces on the technical side. This research used descriptive methodology after gathering data from online and indexed research. The research also mentioned five of these obstacles , and how the Amazon overcomes them, and we will take a look at how the opportunities of the Amazon grow so that they have an effect called the Amazon effect, the research reached an important conclusion that eDesk is the leading help desk for online sellers, specifically designed to meet the exact requirements of e-commerce. The research also found solutions to some of the weaknesses faced by electronic commerce platforms.